Modal Sosial sebagai Katalisator Pengembangan Desa Agrowisata - Aulia Rizky, Nabiilah; Mohammad Fakhruddin Mudzakkir (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to analyze the role of social capital as a catalyst in the development of Punten Village as an agrotourism village in Batu City, East Java. This study uses a qualitative descriptive method with a case study approach. Data were collected through field observations, in-depth interviews with the community and stakeholders, and a review of regional development policy and planning documents. The results show that the social capital of the Punten Village community, reflected in the values ​​of trust, solidarity, social networks, and the culture of mutual cooperation, plays a significant role in strengthening community participation, increasing human resource capacity, and encouraging multi-stakeholder collaboration in agrotourism management. Social capital also functions as a social glue that maintains program sustainability and minimizes conflicts of interest in the development process. The conclusion of this study confirms that the development of agrotourism villages is not only determined by the availability of natural resources, but is highly dependent on the strength of social capital as the main foundation for empowerment and sustainable village development. Keywords: Agrotourism, Community Development, Empowerment, Social Capital.